Fieldwork placement for social work students: what persuades managers to open the agency door? - Hanlen, Patricia Anne (Curtin University, 2014)
The international literature identifies both a shortage of fieldwork placements and meaningful workplace experiences for social work students in developed countries. This exploratory constructivist-interpretative study examines the often overlooked management role and factors that influence responses to requests from schools of social work. Managers from Māori and non- Māori non-statutory organisations in Aotearoa New Zealand were interviewed. The qualitative findings confirm the importance of organisational, cultural and informational factors in fostering safe management decisions.